2000
DOI: 10.1088/0953-8984/12/42/307
|View full text |Cite
|
Sign up to set email alerts
|

Effects of iron doping on the transport and magnetic behaviour in La0.65Ca0.35Mn1-yFeyO3

Abstract: We report on the magnetic and transport measurements in an Fe-doped colossal magnetoresistance compound (La 0.65 Ca 0.35 MnO 3 ). Increased spin disorder and a decrease of T c with increasing Fe content are evident. We find that the resistivity data above T p fits better to a variable range hopping model and the localization length decreases with Fe content. The variations in the critical temperature T c , confinement length, magnetic moment and magnetoresistance show a rapid change at about 4-5% Fe. The maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 27 publications
4
20
0
Order By: Relevance
“…relatively stronger antiferromagnetic superexchange effects. It is noticeable for this particular host composition that the addition of 5% Fe results in a decrease of the critical temperature by only 40 K. For the same Fe ion concentration the T c decreases by over 90 K for the La 0.65 Ca 0.35 MnO 3 composition [18]. However no spin glass state is observed in the latter down to 77 K. This difference in behavior is most probably due to the optimum Mn 3+ -Mn 4+ composition in the La 0.65 Ca 0.35 MnO 3 composition, which is very sensitive to the depletion of the Mn 4+ -Mn 3+ bonds as caused by the Fe.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…relatively stronger antiferromagnetic superexchange effects. It is noticeable for this particular host composition that the addition of 5% Fe results in a decrease of the critical temperature by only 40 K. For the same Fe ion concentration the T c decreases by over 90 K for the La 0.65 Ca 0.35 MnO 3 composition [18]. However no spin glass state is observed in the latter down to 77 K. This difference in behavior is most probably due to the optimum Mn 3+ -Mn 4+ composition in the La 0.65 Ca 0.35 MnO 3 composition, which is very sensitive to the depletion of the Mn 4+ -Mn 3+ bonds as caused by the Fe.…”
Section: Discussionmentioning
confidence: 81%
“…We have previously observed [18] that in the strongly ferromagnetic La 0.70 Ca 0.30 MnO 3 (70-30) composition the ferromagnetic T c is suppressed at about 19 K/Fe% in the range 1-10% of Fe. This is well understood [17] in terms of the increased antiferromagnetism due to the Fe 3+ ions and the reduction in the number of Mn 4+ ions, as a consequence of the Fe addition.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…With the density of states N (E) = 9 × 10 26 m 3 ev −1 (Ref. 25) and T 0 , it is found that the localization length decreases from ξ ≈ 0.066 nm for y = 0, ξ ≈ 0.021 nm for y = 0.05 and ξ ≈ 0.005 nm for y = 0.10, which indicates the increase of the charge-carrier localization intensity. It also indicates that double exchange interaction decreases with the increase of the Fedoping level, possibly due to the formation of magnetic cluster.…”
Section: Electrical Propertiesmentioning
confidence: 93%
“…It is interesting to observe the effect of Fe 3 O 4 layer on the LCMO system at the junction. As temperature is lowered from room temperature, electron finds the LCMO as a low resistance path therefore, LCMO behavior dominates and shows transition-like feature near 150 K. It is to be recalled that Fe doped LCMO system also shifts transition to the lower temperature side [13]. Nevertheless, the oxygen loss from LCMO also cannot be ruled out as the growth of Fe 3 O 4 is taking place at relatively lower oxygen partial pressure than the LCMO film.…”
Section: Article In Pressmentioning
confidence: 99%